2020
DOI: 10.1371/journal.pgen.1009126
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in PIH proteins MOT48, TWI1 and PF13 define common and unique steps for preassembly of each, different ciliary dynein

Abstract: Ciliary dyneins are preassembled in the cytoplasm before being transported into cilia, and a family of proteins containing the PIH1 domain, PIH proteins, are involved in the assembly process. However, the functional differences and relationships between members of this family of proteins remain largely unknown. Using Chlamydomonas reinhardtii as a model, we isolated and characterized two novel Chlamydomonas PIH preassembly mutants, mot48-2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 73 publications
(160 reference statements)
1
21
0
Order By: Relevance
“…Interestingly, this result may relate to the partial co-localization of Dnali1 with Dnai2 ( Figure 2—figure supplement 1C ) and reflects the known intimate link between assembly of ODAs and IDA- c (e.g. Yamaguchi et al, 2018 ; Yamamoto et al, 2020 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, this result may relate to the partial co-localization of Dnali1 with Dnai2 ( Figure 2—figure supplement 1C ) and reflects the known intimate link between assembly of ODAs and IDA- c (e.g. Yamaguchi et al, 2018 ; Yamamoto et al, 2020 ).…”
Section: Resultsmentioning
confidence: 86%
“…2-figure supplement 1C) and reflects the known intimate link between assembly of ODAs and IDA-c (e.g. (Yamaguchi et al, 2018;Yamamoto et al, 2020).…”
Section: Daap1 Is Required For Deployment Of Odas To the Axonemementioning
confidence: 98%
“…One approach is to determine the IDA structure of the last eukaryotic common ancestor (LECA), which is thought to possess cilia (Mitchell, 2017; Satir, Mitchell, & Jekely, 2008). The Chlamydomonas mutant lacking most of IDAs is paralyzed (Huang et al, 1979; Yamamoto et al, 2017, 2020), while mutants lacking all ODAs can still produce ciliary movement at reduced beat frequency (Kamiya, 1988; Mitchell & Rosenbaum, 1985). One interesting idea is that IDA and ODA have evolved together to amplify the efficiency and power for ciliary beating.…”
Section: Remaining Questions and Challengesmentioning
confidence: 99%
“…In addition, mutants lacking all ODAs ( oda strains) can still move albeit at reduce beat frequency (Kamiya, 1988; Mitchell & Rosenbaum, 1985). In contrast, failure in assembly of multiple IDAs (e.g., the pf23 mutant) results in paralyzed cilia or in defective motility (Huang, Piperno, & Luck, 1979; Yamamoto et al, 2017, 2020). Notably, most of the proteins associated with IDAs, including IDA subunits, are conserved in eukaryotic organisms that bear motile cilia (Wickstead & Gull, 2007), and recent studies revealed unexpected links between IDAs and human diseases (Ben Khelifa et al, 2014; Bustamante‐Marin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2-figure supplement 1C) and reflects the known intimate link between assembly of ODAs and IDA- c (e.g. (Yamaguchi et al, 2018; Yamamoto et al, 2020).…”
Section: Resultsmentioning
confidence: 99%